2019
DOI: 10.1093/eurheartj/ehz520
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between coronary plaque morphology of the left anterior descending artery and 12 months clinical outcome: the CLIMA study

Abstract: Aims The CLIMA study, on the relationship between coronary plaque morphology of the left anterior descending artery and twelve months clinical outcome, was designed to explore the predictive value of multiple high-risk plaque features in the same coronary lesion [minimum lumen area (MLA), fibrous cap thickness (FCT), lipid arc circumferential extension, and presence of optical coherence tomography (OCT)-defined macrophages] as detected by OCT. Composite of cardiac death and target segment myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(203 citation statements)
references
References 30 publications
14
164
0
4
Order By: Relevance
“…Indeed, in the CLIMA study, which included 1,003 patients who had C-OCT imaging of the left anterior descending artery, C-OCT-derived plaque characteristics and in particular, the presence of an minimum lumen area <3.5 mm 2 , thin cap fibroatheroma phenotype, a lipid arc >180° and macrophage accumulation enabled prediction of the combined endpoint of cardiac death and target segment revascularization with a positive predictive value of 18.9%. 15 In the present study, we demonstrated that the AC technique enhances the efficacy of EEM border detection (76% vs. 65.5%) compared with C-OCT; using AC-OCT the EEM border was visible for an arc >180° in 76 (38%) images whereas in the C-OCT images it was visible in just 34 (17%). In addition, we found that AC-OCT was more effective than C-OCT in assessing the calcific tissue area.…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, in the CLIMA study, which included 1,003 patients who had C-OCT imaging of the left anterior descending artery, C-OCT-derived plaque characteristics and in particular, the presence of an minimum lumen area <3.5 mm 2 , thin cap fibroatheroma phenotype, a lipid arc >180° and macrophage accumulation enabled prediction of the combined endpoint of cardiac death and target segment revascularization with a positive predictive value of 18.9%. 15 In the present study, we demonstrated that the AC technique enhances the efficacy of EEM border detection (76% vs. 65.5%) compared with C-OCT; using AC-OCT the EEM border was visible for an arc >180° in 76 (38%) images whereas in the C-OCT images it was visible in just 34 (17%). In addition, we found that AC-OCT was more effective than C-OCT in assessing the calcific tissue area.…”
Section: Discussionmentioning
confidence: 48%
“…The same patients showed less advanced coronary artery stenosis, thus suggesting that the co-localization of macrophages and microcalcifications indicates an early phase of the atherosclerotic process which may progress into further calcification and inflammation. Taken together these observations indicate that OCT can provide both morphological and assessment of the level of disease activity, thus identifying patients at higher risk for subsequent coronary events [116].…”
Section: Imaging Plaque Morphologymentioning
confidence: 63%
“…Cumulative evidence has demonstrated that plaque composition determines its vulnerability and enables more accurate risk stratification. Intravascular imaging studies have shown that even single vessel-plaque assessment provides useful prognostic information and identification of patients at risk [2,4,22,23]. Despite the increased cost and the risk of complications associated with intravascular imaging, this strategy may have a value in selected populations with a high cardiovascular risk such as the patients admitted with an acute coronary syndrome where the event rates at 1 year are as high as 20% [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Today, three intravascular imaging modalities are available in the clinical arena (intravascular ultrasound [IVUS], optical coherence tomography [OCT], and nearinfrared spectroscopy [NIRS]-IVUS). These have been studied in large prospective studies and it has been shown that they can provide useful prognostic information and detect vulnerable lesions and high-risk patients that are likely to suffer a cardiovascular event [1,2,4]. Histology studies have shown that NIRS-IVUS has an excellent accuracy in assessing plaque phenotype and it is the best modality for characterising its composition, as it combines an ultrasound probe that gives information about plaque and calcific tissue burden and a NIRS probe that can accurately detect the lipid component [5,6].…”
Section: Introductionmentioning
confidence: 99%